The European Academy of Andrology (EAA) ultrasound study on healthy, fertile men: clinical, seminal and biochemical characteristics - Lotti, Francesco; Frizza, Francesca; Balercia, Giancarlo; Barbonetti, Arcangelo; Behre, Hermann M.; Calogero, Aldo E.; Cremers, Jann‐Frederik; Francavilla, Felice; Isidori, Andrea M.; Kliesch, Sabine; La Vignera, Sandro; Lenzi, Andrea; et al. (Andrology (Oxford), 2020)
Background Infertility affects 7%‐12% of men, and its etiology is unknown in half of cases. To fill this gap, use of the male genital tract color‐Doppler ultrasound (MGT‐CDUS) has progressively expanded. However, MGT‐CDUS still suffers from lack of standardization. Hence, the European Academy of Andrology (EAA) has promoted a multicenter study (“EAA ultrasound study”) to assess MGT‐CDUS characteristics of healthy, fertile men to obtain normative parameters. Objectives To report (a) the development and methodology of the “EAA ultrasound study,” (b) the clinical characteristics of the cohort of healthy, fertile men, and (c) the correlations of both fertility history and seminal features with clinical parameters. Methods A cohort of 248 healthy, fertile men (35.3 ± 5.9 years) was studied. All subjects were asked to undergo, within the same day, clinical, biochemical, and seminal evaluation and MGT‐CDUS before and after ejaculation. Results The clinical, seminal, and biochemical characteristics of the cohort have been reported here. The seminal characteristics were consistent with those reported by the WHO (2010) for the 50th and 5th centiles for fertile men. Normozoospermia was observed in 79.6% of men, while normal sperm vitality was present in almost the entire sample. Time to pregnancy (TTP) was 3.0[1.0‐6.0] months. TTP was negatively correlated with sperm vitality (Adj.r =−.310, P = .011), but not with other seminal, clinical, or biochemical parameters. Sperm vitality and normal morphology were positively associated with fT3 and fT4 levels, respectively (Adj.r = .244, P < .05 and Adj.r = .232, P = .002). Sperm concentration and total count were negatively associated with FSH levels and positively, along with progressive motility, with mean testis volume (TV). Mean TV was 20.4 ± 4.0 mL, and the lower reference values for right and left testes were 15.0 and 14.0 mL. Mean TV was negatively associated with gonadotropin levels and pulse pressure. Varicocoele was found in 33% of men. Conclusions The cohort studied confirms the WHO data for all semen parameters and represents a reference with which to assess MGT‐CDUS normative parameters.